The Role of Parental Engagement in Promoting Early Childhood Development - PHANTHONG, Bounlai; BOUNTHONG, Bounseng; CHANHTHAHONG, Khamxay (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aims to investigate parental roles in supporting preschool child development. The research evaluates five key developmental areas: physical, emotional, social, cognitive, and linguistic. The sample group includes 30 preschool children and their parents. Research tools comprise child development assessment and parent behavior observation forms. Statistical analysis-including frequency, percentage, mean, standard deviation (SD), and correlation coefficient (r)-was employed to test the research hypotheses. The research findings showed that parents play a significant role in children's development. Physical development had the highest level (mean score 10.76/15), followed by social (10.6/15), emotional (9.96/15), cognitive (9.366/15), and language (9.23/15). For parental behavior, physical development promotion was highest (76.66%), followed by cognitive (68.66%), social (67.33%), emotional (65.33%), and language (56.88%). Statistical analysis revealed that parental behavior has a moderately strong positive correlation with statistical significance at a high level (r=0.66, p<0.05), particularly in physical and social areas where children scored higher than in other areas. This study indicates that parents play a key role in promoting preschool children's development and should be supported to gain knowledge and skills in collaboration with educational institutions to develop children comprehensively in all areas requiring special attention for children's future.